If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + -1) + ln(x) = 0 Reorder the terms: ln(-1 + x) + ln(x) = 0 (-1 * ln + x * ln) + ln(x) = 0 (-1ln + lnx) + ln(x) = 0 Multiply ln * x -1ln + lnx + lnx = 0 Combine like terms: lnx + lnx = 2lnx -1ln + 2lnx = 0 Solving -1ln + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-1 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1 + 2x)' equal to zero and attempt to solve: Simplifying -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Add '-2x' to each side of the equation. 2x + -2x = 1 + -2x Combine like terms: 2x + -2x = 0 0 = 1 + -2x Simplifying 0 = 1 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2+2k=14 | | n/3=-13 | | 11=-7+v | | 3x+y=41 | | x/-5=-3.5 | | 27=-3f | | 9=s/2 | | 12m=-24 | | 3y^2+18y+15=0 | | (x-2/7)^2-2(x-2/7)+37=o | | 61/2x31/3 | | r/8=-6 | | 2ax^2+6ax-20a=0 | | x/0.6=7 | | -3(5-9u)=25+7u | | -14=-2h | | 9=-6+d | | 8x-12x=12 | | -15j=20 | | 0.5p=p-5 | | -3(5-9u)=25-7u | | -3x+7x=4 | | -6y=-60 | | -7=b-7 | | -13x+12x=-1 | | 57168=77176/x | | -1t=9 | | x/2=17 | | -4=-2x-6x | | (2n-5)18=450 | | 16s^2=36+36s | | x+3-4x=40 |